2010
DOI: 10.1103/physreva.82.043612
|View full text |Cite
|
Sign up to set email alerts
|

Atom-light crystallization of Bose-Einstein condensates in multimode cavities: Nonequilibrium classical and quantum phase transitions, emergent lattices, supersolidity, and frustration

Abstract: The self-organization of a Bose-Einstein condensate in a transversely pumped optical cavity is a process akin to crystallization: when pumped by a laser of sufficient intensity, the coupled matter and light fields evolve, spontaneously, into a spatially modulated pattern, or crystal, whose lattice structure is dictated by the geometry of the cavity. In cavities having multiple degenerate modes, the quasi-continuum of possible lattice arrangements, and the continuous symmetry breaking associated with the adopti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
187
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(189 citation statements)
references
References 52 publications
(148 reference statements)
2
187
0
Order By: Relevance
“…Even more complex results could be expected from a generalization to fermionic particles [5] or particles with several internal levels [30]. Of course, one of the most interesting aspects and motivations of this approach is the fact that only minor additions to current experimental setups are required and the theoretical model for the current generations of experiments have proven to be surprisingly accurate and reliable [6,8,17,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more complex results could be expected from a generalization to fermionic particles [5] or particles with several internal levels [30]. Of course, one of the most interesting aspects and motivations of this approach is the fact that only minor additions to current experimental setups are required and the theoretical model for the current generations of experiments have proven to be surprisingly accurate and reliable [6,8,17,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A particular interesting generalization was introduced by considering this ordering phenomenon in degenerate multi-mode cavity fields and restricting the degrees of freedom of the particle motion to a 2D plane [16]. This opened a new possible route to study a wealth of important quantum solid state phenomena like emergent crystallinity, liquid crystalline phases [16,17] or quantum neural network models [18] in a well controllable atom-optical configuration. Due to the inherent complexity and technical difficulty of degenerate multi-mode setups, which require at least a 2D geometry, theoretical modeling as well as experimental implementations of such setups are very challenging and have, to our knowledge, not been implemented to date.…”
Section: Introductionmentioning
confidence: 99%
“…We also indicate how to relate the operators of the master equation (2) to the field content and choice of time contour in a Keldysh action (see also Refs. [15,18,42]). …”
Section: Keldysh Approach For Cavity Vacuummentioning
confidence: 99%
“…To treat the interplay between external driving, dissipation and many-body interactions in a more general setting, we next develop a unified approach to describe phase transitions in open quantum systems based on Keldysh path integrals [15][16][17][18][19][20][21]. This approach is used to analyze the driven Dicke model in the presence of finite-size effects and atomic dissipative processes.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a quantum phase transition in the universality class of the (solvable) infinite-range Ising quantum spin glass [13,14] occurs, potentially enabling comparison between experiment and the theory of spin glasses. In a related paper [15][16][17], Gopalakrishnan et al provided experimental details and detection methods for the spin glass phase.…”
Section: Introductionmentioning
confidence: 99%